Exploring the role Delaware plays as a domestic tax haven - Dyreng, Scott D.; Lindsey, Bradley P.; Thornock, Jacob R. (Journal of Financial Economics, 2013)
We examine whether Delaware is a domestic tax haven. We find that taxes play an economically important role in determining whether U.S. firms locate subsidiaries in Delaware and that a Delaware-based state tax avoidance strategy lowers state effective tax rates by between 0.7 and 1.1 percentage points, on average. The tax savings represent a 15–24% decrease in the state income tax burden and translate to an increase in net income of 1.04–1.47%. However, we find that the tax benefits of Delaware tax strategies are diminishing over time in response to initiatives by state governments to limit multistate tax avoidance.